Etika Produksi Dalam Maqashid Syariah (Studi Kasus: Rumah Makan Angin Berhembus Panyabungan) - Indah Permata Sari; Rozalinda Rozalinda; Nora Zulvianti (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This study evaluates the implementation of Maqashid Syariah Principles protecting religion (hifz ad-din) life (hifz an-nafs), wealth (hifz al-mal), and the environment (hifz al-biah) in restaurant’s production practices. A qualitative case study approach was used, with primary data from interviews with owner, employees, and customers, alongside direct observations and secondary data from operational documents. The results show that Rumah Makan Angin Berhembus applies hifz ad-din and hifz an-nafs by serving halal, thayyib food and maintaining cleanliness in production. The al-mal principle is reflected in the use of local ingrediets. However, there are gaps in the hifz al-biah principle, particularly in waste management and environmentally friendly production. Can serve as a model for other culinary businesses, promoting fairness and sustainability in their operations.